The Large Marseillevirus Explores Different Entry Pathways by Forming Giant Infectious Vesicles - Arantes, Thalita Souza (J Virol, 2016)
Triggering the amoebal phagocytosis process is a sine qua non condition for most giant viruses to initiate their replication cycle and consequently to promote their progeny formation. It is well known that the amoebal phagocytosis process requires the recognition of particles of >500 nm, and most amoebal giant viruses meet this requirement, such as mimivirus, pandoravirus, pithovirus, and mollivirus. However, in the context of the discovery of amoebal giant viruses in the last decade, Marseillevirus marseillevirus (MsV) has drawn our attention, because despite its ability to successfully replicate in Acanthamoeba, remarkably it does not fulfill the >500-nm condition, since it presents an ∼250-nm icosahedrally shaped capsid. We deeply investigated the MsV cycle by using a set of methods, including virological, molecular, and microscopic (immunofluorescence, scanning electron microscopy, and transmission electron microscopy) assays. Our results revealed that MsV is able to form giant vesicles containing dozens to thousands of viral particles wrapped by membranes derived from amoebal endoplasmic reticulum. Remarkably, our results strongly suggested that these giant vesicles are able to stimulate amoebal phagocytosis and to trigger the MsV replication cycle by an acidification-independent process. Also, we observed that MsV entry may occur by the phagocytosis of grouped particles (without surrounding membranes) and by an endosome-stimulated pathway triggered by single particles. Taken together, not only do our data deeply describe the main features of MsV replication cycle, but this is the first time, to our knowledge, that the formation of giant infective vesicles related to a DNA virus has been described. IMPORTANCE Triggering the amoebal phagocytosis process is a sine qua non condition required by most giant viruses to initiate their replication cycle. This process requires the recognition of particles of >500 nm, and many giant viruses meet this requirement. However, MsV is unusual, as despite having particles of ∼250 nm it is able to replicate in Acanthamoeba. Our results revealed that MsV is able to form giant vesicles, containing dozens to thousands of viral particles, wrapped in membranes derived from amoebal endoplasmic reticulum. Remarkably, our results strongly suggest that these giant vesicles are able to stimulate phagocytosis using an acidification-independent process. Our work not only describes the main features of the MsV replication cycle but also describes, for the first time to our knowledge, the formation of huge infective vesicles in a large DNA viruses.